DETERMINATION OF WOOD SPECIMENS USING ISOSTRAIN PATTERNS GENERATED FOR MOIRÉ TECHNIQUE - ALBIERO, DANIEL; RODRIGUES, SILVESTRE; BERALDO, ANTONIO LUDOVICO; MACIEL, ANTONIO JOSÉ DA SILVA; FABBRO, INÁCIO MARIA DAL; MAZETTI, VITOR; GAMERO, ANTONIO CARLOS (Revista Brasileira de Engenharia de Biossistemas, 2007)
Brazilian forest's wood characterization requires very complex tasks due to the large number of species available throughout the whole national territory. Available wood characterization methods demand relatively long test timing or they are quite costly and sometimes they exhibit a lack of precision. This research work reports a new method for wood characterization based on a moiré photoelastic technique. Such family of methods is able to generates the microtopography of the object under study and also the stress-strain distribution under a specific loading condition. Moiré means wave like pattern generated when screens of same mesh density are superposed. It is reported the application of a moiré technique in magnifying displacements, being also suitable as a photoelastic method. Three specimens of different wood species were submitted to axial loads before failure meanwhile a grid of specific mesh density was projected onto the object. The experimental setup this work included a digital camera to capture the moiré patterns generated by the projection of a regular grid onto the object and processed by involving software named Gimp and Idrisi. Tests were conducted in the Faculty of Agricultural Engineering at Campinas University, Campinas, SP, Brazil.